The Polycystin complex mediates WNT/Ca(2+) signaling - Kim, Seokho (Nat Cell Biol, 2016)
WNT ligands induce Ca(2+) signaling on target cells. PKD1 (Polycystin 1) is considered an orphan, atypical G protein coupled receptor complexed with TRPP2 (Polycystin 2 or PKD2), a Ca(2+)-permeable ion channel. Inactivating mutations in their genes cause autosomal dominant polycystic kidney disease (ADPKD), one of the most common genetic diseases. Here, we show that WNTs bind to the extracellular domain of PKD1 and induce whole cell currents and Ca(2+) influx dependent on TRPP2. Pathogenic PKD1 or PKD2 mutations that abrogate complex formation, compromise cell surface expression of PKD1, or reduce TRPP2 channel activity suppress activation by WNTs. Pkd2(−/−) fibroblasts lack WNT-induced Ca(2+) currents and are unable to polarize during directed cell migration. In Xenopus embryos, PKD1, Dishevelled 2 (DVL2), and WNT9A act within the same pathway to preserve normal tubulogenesis. These data define PKD1 as a WNT (co)receptor and implicate defective WNT/Ca(2+) signaling as one of the causes of ADPKD.